2020
DOI: 10.1002/mp.14320
|View full text |Cite
|
Sign up to set email alerts
|

Auto‐segmentation of organs at risk for head and neck radiotherapy planning: From atlas‐based to deep learning methods

Abstract: Radiotherapy (RT) is one of the basic treatment modalities for cancer of the head and neck (H&N), which requires a precise spatial description of the target volumes and organs at risk (OARs) to deliver a highly conformal radiation dose to the tumor cells while sparing the healthy tissues. For this purpose, target volumes and OARs have to be delineated and segmented from medical images. As manual delineation is a tedious and time-consuming task subjected to intra/interobserver variability, computerized auto-seg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
109
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(110 citation statements)
references
References 155 publications
(753 reference statements)
1
109
0
Order By: Relevance
“…It can not only shorten the time needed to exploit the anatomy but also allow experts to devote time to optimize RT treatment planning so that the OARs could be less irradiated. In recent years, various image segmentation techniques have been proposed, resulting in more accurate and efficient image segmentation for clinical diagnosis and treatment (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…It can not only shorten the time needed to exploit the anatomy but also allow experts to devote time to optimize RT treatment planning so that the OARs could be less irradiated. In recent years, various image segmentation techniques have been proposed, resulting in more accurate and efficient image segmentation for clinical diagnosis and treatment (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“… The box plot results of auto-segmentation of OARs in HNC reported in terms of the Dice coefficient ( 22 ). The red mark dots are the Dice coefficient in our second phase training results.…”
Section: Discussionmentioning
confidence: 99%
“…The major evident advantage of DL-based autosegmentation is that it can systematically learn the adequate features, which was never possible with the naked eye for segmentation, from a large amount of a given training database. Then, the same features can be searched automatically in a validation set ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…CNN-based methods have proven highly accurate for automated segmentation in magnetic resonance imaging (MRI) of the prostate, CT of the liver and bladder, and PET/CT images of skeletal structures [7] , [8] , [9] , [10] , [11] . Furthermore, in the field of radiation oncology, studies on head and neck cancer have adhered to the fact that correctly implemented AI techniques generates better efficiency and standardization of treatment for patients with head and neck cancer [12] , [13] , [14] . In the case of rectal cancer, a previous study evaluated the auto-segmentation of target volume and OAR, and showed varying segmentation accuracy based on the Dice similarity coefficient ranging from 61.8% (colon) to 93.4% (bladder) [15] .…”
Section: Introductionmentioning
confidence: 99%